Brain of the blind: transcriptomics of the golden-line cavefish brain. Issue 6 (12th January 2018) - Meng, Fanwei; Zhao, Yahui; Titus, Tom; Zhang, Chunguang; Postlethwait, John H
Abstract: The genus Sinocyclocheilus (golden-line barbel) includes 25 species of cave-dwelling blind fish (cavefish) and more than 30 surface-dwelling species with normal vision. Cave environments are dark and generally nutrient-poor with few predators. Cavefish of several genera evolved convergent morphological adaptations in visual, pigmentation, brain, olfactory, and digestive systems. We compared brain morphology and gene expression patterns in a cavefish Sinocyclocheilus anophthalmus with those of a closely related surface-dwelling species S. angustiporus . Results showed that cavefish have a longer olfactory tract and a much smaller optic tectum than surface fish. Transcriptomics by RNA-seq revealed that many genes upregulated in cavefish are related to lysosomes and the degradation and metabolism of proteins, amino acids, and lipids. Genes downregulated in cavefish tended to involve "activation of gene expression in cholesterol biosynthesis" and cholesterol degradation in the brain. Genes encoding Srebfs (sterol regulatory element-binding transcription factors) and Srebf targets, including enzymes in cholesterol synthesis, were downregulated in cavefish brains compared with surface fish brains. The gene encoding Cyp46a1, which eliminates cholesterol from the brain, was also downregulated in cavefish brains, while the total level of cholesterol in the brain remained unchanged. Cavefish brains misexpressed several genes encoding proteins in the hypothalamus–pituitary axis, including Trh, Sst, Crh, Pomc, and Mc4r. These results suggest that the rate of lipid biosynthesis and breakdown may both be depressed in golden-line cavefish brains but that the lysosome recycling rate may be increased in cavefish; properties that might be related to differences in nutrient availability in caves.